Luminescence and photocatalytic studies of Sm3+ ion doped SnO2 nanoparticles - Singh, L. P.; Luwang, Meitram Niraj; Srivastava, S. K. (New Journal of Chemistry, 2014)
Sm3+ ion doped tetragonal SnO2 nanoparticles have been synthesized by the polyol method and its concentration and annealing effects on photoluminescence properties are studied. The XRD results show the changes of lattice parameters with the incorporation of the Sm3+ ion into the SnO2 host lattices. Fourier transform infrared (FTIR) data indicate the formation of a Sn-O bond and capping of the nanoparticles by ethylene glycol. The broad emission peaks observed around 350 to 550 nm are attributed to the emission from defects or traps present in the host SnO2. The typical emission peaks of the Sm3+ ion are observed and there is efficient energy transfer between the host, SnO2 and the dopant, Sm3+ ion. Further, the prepared samples are experimented towards the photocatalytic behavior on selected triphenylmethane dyes, Ethyl Violet (EV) and Brilliant Green (BG). The degradation of dyes was found to be enhancing in the presence of Sm3+ ions as it suppress the e e(CB)(-) and h(VB)(+) recombination.

Liquid crystalline nanoconfined growth of PANI on rGO for enhanced electrochemical glucose sensing - Tawade, Anita K.; Kumar, Praveen; Tayade, Shivaji N.; Sharma, Geetarani K.; Luwang, Meitram Niraj; Sharma, Kiran Kumar K. (Nanoscale, 2026)
We report here a new strategy for the successful synthesis of a hybrid 2D nanocomposite via the in situ functionalization of graphene oxide (GO) with aniline monomers in a bi-solvent swollen liquid crystalline lamellar mesophase (SLCLM) nanoreactor. The synthesized nanocomposite product revealed possible simultaneous reactions at the edge and basal plane of GO. A mechanism for the transformation via simultaneous nucleophilic attack and spontaneous polymerization, forming a reduced graphene oxide-polyaniline (rGO-PANI) nanocomposite, is proposed. The multistep plausible reaction mechanism for the functionalization of the GO edge -COOH group is achieved by successful synthesis, followed by isolation and characterization of the N-phenyl anthranilic acid derivative as an intermediate product. Furthermore, the detection of CO2 evolution as a by-product during the reaction complements the plausible mechanism for the incorporation of (-C Xi C-) graphyne-type edges and formation of new -C-N- and O-H bonds in the rGO-PANI nanocomposite. These results are supported by FT-IR, Raman, XPS, SAXS, and C-13 NMR spectroscopy analyses. A reduced graphene oxide-polyaniline (rGO-PANI) modified glassy carbon electrode was developed for glucose sensing, exhibiting a wide linear range (0.554-10 & micro;M), low detection limit (50 pM), and high sensitivity (372 660 & micro;A mM(-1) cm(-2)). The sensor demonstrated excellent selectivity against common interferents (ascorbic acid, uric acid, and dopamine), reproducibility (RSD < 5%), and stability over 10 000 s with minimal signal loss. The detection of glucose from human metabolites, such as urine and sweat, achieved 98-100% recoveries for spiked glucose, confirming its practical applicability. These results establish rGO-PANI as a robust platform for sensitive and selective glucose detection.